Evaluation of Gamma-Glutamyl Transferase as a Diagnostic Biomarker for Prostate Cancer in Iraqi Patients - Abdulameer Ali AL-Dahhan, Najlaa; Hasan Hadi, Hadi; Abdulzahraa, Zahraa Hamza (Asian Pacific Journal of Cancer Biology, 2025)
Background: Prostate cancer remains the most prevalent malignancy and leading cause of cancer-related mortality among men worldwide. This study investigated the diagnostic potential of serum gamma-glutamyl transferase (GGT) as a novel biomarker for Prostate cancer detection compared to established markers. Methods: A case-control study was conducted with 80 histologically confirmed Prostate cancer patients and 80 age-matched healthy controls. Serum levels of prostate-specific antigen (PSA), malondialdehyde (MDA), paraoxonase 1 (PON1), arylesterase (ARE), and GGT were quantified using ELISA. Results: Significantly elevated levels of PSA, MDA, and PON1 were observed in prostate cancer patients compared to controls (p ≤ 0.001 for all). In contrast, ARE activity was significantly reduced in patients (p ≤ 0.001). Serum GGT levels were significantly higher in prostate cancer patients than in healthy controls, though this difference did not reach statistical significance (p = 0.104). The mean difference in GGT levels between prostate cancer patients and controls was 16.17 U/L (95% CI: −2.65 to 34.99), which was not statistically significant (p = 0.104). In contrast, PSA levels exhibited a significant mean difference of 79.67 ng/mL (95% CI: 27.87 to 131.47; p ≤ 0.001). Multivariate analysis revealed a non-significant inverse correlation between MDA and GGT in the prostate cancer group (r = −0.18, p = 0.12). Conclusions: The use of serum GGT as an independent prognostic biomarker for prostate cancer has limited clinical utility due to its poor specificity and sensitivity, despite its significantly elevated levels in patients. In contrast, oxidative stress markers (MDA, PON1, ARE) and PSA have shown stronger prognostic potential, with PSA remaining the most effective single marker. The observed trends highlight the potential of oxidative stress biomarkers as complementary tools.